Within the red lines: a qualitative case study of food insecurity among homeless people in one of Kansas City’s historically redlined districts - Ramirez, Jessica Marie (Kansas State University, 2023)
Deepening inequality in the United States has led to increased homelessness and food insecurity. Most research on the links between food insecurity and homelessness in the United States is guided by cumulative risk and stress process theories. Both theories shed light on the individual and community-level factors that influence variations in food insecurity among homeless populations; however, food justice researchers criticize such models for focusing solely on contemporary factors without accounting for historical systemic injustices. At the same time, little research has been conducted to fill the gap in knowledge about the connections between historical systemic inequalities and contemporary food insecurity among homeless populations. How do contemporary and historical forces of inequality interact to affect people’s experiences with both homelessness and food insecurity? In my study, I investigate how redlining (racial residential segregation) as a mechanism of inequality affects people’s experiences of homelessness and food insecurity. Based on ethnographic observations and 21 oral history style interviews with homeless shelter workers and homeless people experiencing food insecurity in one of Kansas City, Missouri's most historically redlined districts, District 25, I find that the type of homelessness an individual experiences affects their food insecurity. More specifically, my findings show how the relative proximity of where people sleep to centers providing food on specific schedules, the amount of time people spend looking for a place to sleep, and people’s access to information and community connectedness impact their food insecurity. I also find that the concentration of emergency resources in District 25 paired with hostile architecture and violence emanating from outside the district confine people to an area where decades of disinvestment have diminished food and housing security.
Keywords: Homelessness; Food insecurity; Redlining; Social inequality; Qualitative; Case study